Mencermati Kampanye Pileg 2009: Gradasi Peran Partai dan Gej ala Pragmatisme - Noor, Firman (Pusat Penelitian Politik, 2009)
The 2009 election campaign for legislative bodies provides many lessons for Indonesian The phenomena occurred in this occasion are the gradation of theparties role and the rise ofpragmatism This paper discusses factors behind those phenomena in which the existence of the new regulation internal condition ofpolitical parties and the quality of the member ofpolitical parties are believed to play a salient role.